Preparation and Properties of Cellulose Nanocrystal Based Structurally Colored Radiative Cooling Composite Films - Volkov, Mikhail (Journal of Green Energy and Environmental Engineering, 2023)
Radiative cooling is a green, low-carbon, and sustainable cooling strategy that lowers its own temperature by emitting heat into outer space. Most radiative cooling materials exhibit monotonous color appearances, mostly white or transparent, and the addition of traditional colorants causes heat absorption, thereby reducing radiative cooling performance. In this study, cellulose nanocrystal/polyethylene glycol (CNC/PEG) composite radiative cooling films with tunable structural colors were prepared via a self-assembly method. These composite films were subsequently combined with porous cellulose acetate (CA) films to obtain structurally colored radiative cooling bilayer composite films. The results indicate that the CNC/PEG composite films exhibit vivid structural colors with distinct birefringence phenomena. As the PEG content increases, the pitch of the composite film structure enlarges, and the color shifts from blue-green to red. The CNC/PEG structural color composite film achieves a maximum reflectance of up to 68.5% in the visible light band and an emissivity of up to 93% in the atmospheric window band, demonstrating an ambient cooling effect of approximately 3.4 °C. The CNC/PEG-CA bilayer composite film attains a maximum reflectance of up to 91.8% in the visible light band and an emissivity of up to 32.2% in the atmospheric window band. Compared with the single-layer composite film, the bilayer composite film exhibits superior cooling performance, with a temperature difference of approximately 14.3 °C relative to the ambient temperature. In outdoor tests, the composite film achieves a cooling effect of approximately 2 °C, while the bilayer composite film achieves a cooling effect of approximately 6 °C compared to the ambient temperature.